On-line recognition of developing control chart patterns quarter wave stack model simulation for optical edge filter design using octave - Mohammed Bello, Abubakar (2019)
Optical filter by virtue o f their special functions to block a particular wavelength or range o f w avelength and transm it the rest o f the spectrum have received research attention for the past few decades. Recently, optical filter based on m ultilayer coating are more focused due to potential to manipulate filter properties by changing layer thickness in order to apply in various fields. Quarter wave stack (QWS) model is one o f the approaches to design optical filter such as edge filter. However, to obtain desire minimum specification need an optimization. Therefore, in this study aims to design optical edge filter based QWS model by optical matrix methods in Octave software and fabricate it based on the result obtained using RF magnetron sputtering. Prior to the design, M oS2 and Si are being choose for high (H) and low (L) refractive index materials respectively. The optimum tw enty-four (24) num ber o f layers are determined by calculating maximum transm ittance obtained. The Rayleigh w avelength (Aex ) o f 405 nm ,532 nm and 633 nm are selected and ‘glass|12H L|air’ configuration is set for the design simulation. Then, the cut-on wavelength (Acut-on) and cut-off wavelength ( Acu t-o / / ) o f successful designed optical edge filter are measured. The result shows that the cut-on wavelength o f 408.11 nm, 536 nm and 640.25 nm with minimum effective transm ission (MET) o f 32.3%, 31.3% and 32% respectively are obtained. Edge filter for A cut-on = 633 nm A ex is selected and fabricated to obtained layer thickness same as generated from the simulation. Afterwards, the fabricated filter is characterized by U V -V is spectroscopy and field emission scanning electron microscope (FESEM). The result from U V-Vis spectra showed that A cut-on of fabricated filter at 700 nm with M ET o f 36%. Moreover, the Film etric result give the A cut-on at 640 nm w ith 30% M ET for A ex = 633 nm which is very close as compare to the simulated result. In conclusion, the result o f the present study shows a good correlation between simulation and the Film etric methods w ith a bit deviation value o f A cut-on for fabricated filter.